2020
DOI: 10.3390/cancers12020445
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of SFRP1: The Dual Roles in Human Cancers

Abstract: Secreted frizzled-related protein 1 (SFRP1) is a gene that belongs to the secreted glycoprotein SFRP family. SFRP1 has been classified as a tumor suppressor gene due to the loss of expression in various human cancers, which is mainly attributed by epigenetic inactivation via DNA methylation or transcriptional silencing by microRNAs. Epigenetic silencing of SFRP1 may cause dysregulation of cell proliferation, migration, and invasion, which lead to cancer cells formation, disease progression, poor prognosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 101 publications
4
83
0
Order By: Relevance
“…The expression levels of sFRP4 were downregulated by more than nine-fold in the CRC cell lines compared with the control cell line. (21). The transcriptional expression levels of components of the Wnt signaling pathway were assessed using gene array analysis of whole genome expression in SW1116, SW480, HCT116 and CCC-HIE-2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of sFRP4 were downregulated by more than nine-fold in the CRC cell lines compared with the control cell line. (21). The transcriptional expression levels of components of the Wnt signaling pathway were assessed using gene array analysis of whole genome expression in SW1116, SW480, HCT116 and CCC-HIE-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several decades, advances have been made in the understanding of cancer epigenetics, particularly for aberrant DNA methylation, microRNA and non-coding RNA dysregulation, and alterations in histone modification states (14). sFRPs have been recognized for their potential to sequester Wnt ligands away from their receptor complexes and ultimately antagonize Wnt signaling (4,11,21). Analysis of sFRP hypermethylation may have diagnostic and prognostic value for the detection and management of CRC (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Although cluster 0 and 2 appeared as a continuum of cells, significant differences in gene expression are evident (Figure 1D and 2B). For example, while all luminal progenitor cells expressed Secreted Fizzled Related Protein 1 (SFRP1), a modulator of Wnt signaling (Baharudin et al, 2020), genes such as SLP1, ANXA1, RARRES1, KLK5, and KRT15 were enriched in cluster 2. KRT14 and KRT17 expression were enriched in cluster 2 but not in cluster 0.…”
Section: Resultsmentioning
confidence: 99%
“…In esophageal, lung, bladder and oral cancers, NID2 methylation and reduced tissue expression are observed [43], suggesting biomarker context of NID2 may diverge in tumor tissue and EV compartments. SFRP1 (Secreted frizzled-related protein 1) is a glycoprotein modulator of Wnt-signaling that has been observed to play both tumor suppressor and oncogenic roles in a number of human cancers and to also be subject to epigenetic regulation via DNA methylation or microRNA transcriptional silencing [44]. A recent study demonstrated functional relevance of exosome-associated SFRP family proteins and that human lung cancer cells take up SFRP-containing exosomes, whereby SFRPs co-localize with β-catenin in both the cytoplasm and nucleus to mediate β-catenin/TCF-mediated transcription of Wnt target genes known to effect cancer stem cell properties [45].…”
Section: Discussionmentioning
confidence: 99%